Merkel Cell Carcinoma with Spontaneous Regression: A Case Report and Immunohistochemical Study - Hitoshi Terui; Taku Fujimura; Aya Kakizaki; Sadanori Furudate; Setsuya Aiba (Karger Publishers, 2016)
Merkel cell carcinoma (MCC) is an aggressive neuroendocrine carcinoma that only rarely regresses spontaneously. Since little is known about the immunological mechanisms involved in the spontaneous regression of MCC, we describe a case of MCC with spontaneous regression and employed immunohistochemical staining for cytotoxic and immunosuppressive molecules to investigate possible mechanisms involved in the spontaneous regression of MCC. Interestingly, compared to conventional MCC, tumor-infiltrating lymphocytes in MCC with spontaneous regression contained higher numbers of CD8+ cells and granulysin-bearing cells and lower numbers of CD206+ cells. Our present study suggests one of the possible reasons for the spontaneous regression of MCC.